EMERGENCE AND DEVELOPMENT OF ISLAMIC REVIVALIST TREND IN YORUBALAND OF NIGERIA - Nafiu Ahmed Arikewuyo (Journal of Islamic Studies and Humanities, 2022)
The presentation of religion in its true picture of revelation has always been threatened by human interpolation, manipulation, and misinterpretation. To save religion from the nemesis of the above, the Prophet of Islam guaranteed that Allah shall be raising in every Muslim generation a reformer who will redefine religion in its original form. Hence, the expectation of a reformist trend at every particular point of spiritual retrogression by Muslims has become a recurring convention. The present research attempts to examine the aforementioned trend in Yorubaland of Nigeria. The research is a mixture of library and field research and adopts historical and descriptive methods. It discovered that the prophetic tradition on the rise of a reformer could not be limited in exclusion of others to mean a personified or individual description. Rather it can also render the meaning of the emergence of a new religious trend pursued by a large congregation of believers. The research also reveals that the comprehensive take-off of the reformist trend in Yorubaland started in the 70s of the last century with a noticeable influence from abroad. It recommends further detailed studies on the challenges and prospects of the new emerging revivalist trends in the region.